Discovery of gamma-ray emission from the extragalactic pulsar wind nebula N 157B with H.E.S.S. - Abramowski, A. (2012)
We present the significant detection of the first extragalactic pulsar wind nebula (PWN) detected in gamma rays, N 157B, located in the large" "Magellanic Cloud (LMC). Pulsars with high spin-down luminosity are found to power energised nebulae that emit gamma rays up to energies of several tens of TeV. N 157B is associated with PSR J0537−6910, which is the pulsar with the highest known spin-down luminosity. The High Energy Stereoscopic System telescope array observed this nebula on a yearly basis from 2004 to 2009 with a dead-time corrected exposure of 46 h. The gamma-ray spectrum between 600 GeV and 12 TeV is well-described by a pure power-law with a photon index of 2.8 ± 0.2stat ± 0.3syst" "and a normalisation at 1 TeV of (8.2 ± 0.8stat ± 2.5syst ) × 10−13 cm^{−2} s^{−1} TeV^{−1} . A leptonic multi-wavelength model shows that an energy of about 4 × 1049 erg is stored in electrons and positrons. The apparent eﬃciency, which is the ratio of the TeV gamma-ray luminosity to the pulsar?s spin-down luminosity, 0.08% ± 0.01%, is comparable to those of PWNe found in the Milky Way. The detection of a PWN at such a large distance is possible due to the pulsar?s favourable spin-down luminosity and a bright infrared photon-field serving as an inverse-Compton-scattering target for accelerated leptons. By applying a calorimetric technique to these observations, the pulsar?s birth period is estimated to be shorter than 10 ms.